Betel Eating Culture on Periodontal Health Batak Karo Women - Dicky Andreas Simbolon,; M.Aldri Romatua Pohan,; Muammar Rifqi,; Muhammad Ghazi Al Ghifari Lubis, (Indonesian Journal of Medical Anthropology, 2024)
The culture of eating betel has become a strong tradition in Batak Karo society, especially among women. This tradition is not only an ordinary habit, but also has important social, spiritual and identity meaning. However, on the other hand, the ingredients used in eating betel, such as betel leaves, areca nut, lime, and tobacco, are known to have potential risks to oral health, especially periodontal health. This study aims to explore the relationship between betel eating culture and periodontal health status in Batak Karo women. A literature study was carried out to look for previous research and review the results of previous research. The research results show that the practice of eating betel has a very important cultural value in the lives of the Batak Karo people, especially as a symbol of social status, respect and beauty for women. However, it was found that the majority of Karo Batak women experienced poor periodontal conditions, such as gingivitis, periodontitis and premature tooth loss.